2015
DOI: 10.1104/pp.15.00879
|View full text |Cite
|
Sign up to set email alerts
|

The RING Finger Ubiquitin E3 Ligase OsHTAS Enhances Heat Tolerance by Promoting H2O2-Induced Stomatal Closure in Rice

Abstract: Heat stress often results in the generation of reactive oxygen species, such as hydrogen peroxide, which plays a vital role as a secondary messenger in the process of abscisic acid (ABA)-mediated stomatal closure. Here, we characterized the rice (Oryza sativa) HEAT TOLERANCE AT SEEDLING STAGE (OsHTAS) gene, which plays a positive role in heat tolerance at the seedling stage. OsHTAS encodes a ubiquitin ligase localized to the nucleus and cytoplasm. OsHTAS expression was detected in all tissues surveyed and peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(98 citation statements)
references
References 89 publications
3
86
0
1
Order By: Relevance
“…Multiple studies have shown that the ability to clean up unfolded proteins corresponds to the ability of plants to survive exposure to extreme HT. For example, plants deficient in the expression of proteasome subunits (Li et al ), E3 ligases, and autophagy‐related genes (Zhou et al , ; Liu et al ; Gil et al ) are susceptible to HS. Moreover, transgenic plants overexpressing genes encoding either ubiquitin (Tian et al ) or ubiquitin E3 ligases (Lim et al ; Liu et al ; Liu et al ) exhibit enhanced basal and/or acquired heat tolerance.…”
Section: Heat Shock Signaling Mechanismsmentioning
confidence: 99%
“…Multiple studies have shown that the ability to clean up unfolded proteins corresponds to the ability of plants to survive exposure to extreme HT. For example, plants deficient in the expression of proteasome subunits (Li et al ), E3 ligases, and autophagy‐related genes (Zhou et al , ; Liu et al ; Gil et al ) are susceptible to HS. Moreover, transgenic plants overexpressing genes encoding either ubiquitin (Tian et al ) or ubiquitin E3 ligases (Lim et al ; Liu et al ; Liu et al ) exhibit enhanced basal and/or acquired heat tolerance.…”
Section: Heat Shock Signaling Mechanismsmentioning
confidence: 99%
“…Recently, it was reported that ROS can induce stomatal closure through an ABA‐independent pathway in rice ( Oryza sativa ). The SNAC1‐targeted gene OsSRO1c positively controls H 2 O 2 ‐induced stomatal closure by regulating hydrogen peroxide level in rice, and the E3 ligase OsHTAS can promote heat tolerance by modulating H 2 O 2 ‐induced stomatal closure in rice (Liu et al ., ; You et al ., ). However, 35S: OsASR5 plants were more sensitive to exogenous ABA treatment, activating the production of H 2 O 2 (Li et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Rice (Oryza sativa), as a dietary staple for almost two-thirds of the world's population, is one of the most important agricultural crops. Recently, some genes have been used successfully to improve the tolerance of rice to stresses [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%